2021
DOI: 10.1101/2021.02.18.431928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of RICs iron donation for iron-sulfur cluster biogenesis

Abstract: Escherichia coli YtfE is a di-iron protein, of the widespread RIC family, with capacity to donate iron, which is a crucial component of the biogenesis of the ubiquitous family of iron-sulfur proteins. Herein we identify in E. coli a previously unrecognized link between the YtfE protein and the major bacterial system for iron-sulfur cluster (ISC) assembly. We show that YtfE establishes protein-protein interactions with the scaffold IscU, where the transient cluster is formed, and the cysteine desulfurase IscS. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Transcriptomic analysis of a ∆norR mutant indicated that norA is the only enzyme-encoding gene in the NorR regulon; this is noteworthy because NorR typically also regulates norB and/or hmpX (53,55). The roles and regulation of RIC/NorA homologs have been studied in a few human pathogens but have not been considered in a plant pathogen (8,28,36,40,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic analysis of a ∆norR mutant indicated that norA is the only enzyme-encoding gene in the NorR regulon; this is noteworthy because NorR typically also regulates norB and/or hmpX (53,55). The roles and regulation of RIC/NorA homologs have been studied in a few human pathogens but have not been considered in a plant pathogen (8,28,36,40,44).…”
Section: Discussionmentioning
confidence: 99%
“…A second protective mechanism involves NO-inducible Repair of Iron Centers (RIC) di-iron proteins. RICs use a hemerythrin-like domain to decrease oxidative damage by interacting with iron storage proteins like Dps and IscU to deliver iron to damaged Fe-S clusters (36,(40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%